Islamic Education Reform in Facing the Globalization Era - Wahib, Ahmad (Jurnal Paradigma, 2021)
This writing discuss about Islamic education which gets some crusial challenges in globalization era Islamic teaching plays important role in glonalozation. Seince globalization itself has positive also negative in Islamic teaching and training. This reformation of Islamic teaching could strive for raising better vision of Islamic teaching for building and upgrading quality of human being and moslem society in globalization that ought to refer to both Al Koran and Al Hadith as source of its teaching. The goal of this current research is to describe reformation of Islamic teaching in facing globalization. Data of this paper is literatature fact which is analyzed trough descriptive. The result of this writingshows that globalization can be opportunity and also challenge for Islamic teaching. The stream of globalization is not an opponent or companion for Islamic teaching, on the other hand being as motivator. If slamic teaching takes position non global, it will not move and it will undergo blocking of intellectual. On the contrary, if Islamic teaching involves to globalization era, Islamic identities will be gone. Thus, Islamic teaching ought to take partto measure globalization era, it means by orientation and values of Islamic teaching in order to could be reformed, adopted and developed.